The role of motor processes in mental rotation: selective shaping of cognitive processing via specific sensorimotor experience. Issue 2 (3rd April 2019) - Habacha, Hamdi
ABSTRACT: The involvement of motor processes in mental rotation is experience-dependent: different levels of expertise in sensorimotor interactions lead to different strategies in mental rotation. In the present study, wrestlers, gymnasts, and nonathletes physically rotated objects that were either light (wooden) or heavy (lead) but otherwise having the same sizes and shapes. They then performed a mental rotation task using photographs of these objects in which the material and therefore the weight was visible. I hypothesized that wrestlers would rely more heavily on experience-based sensorimotor strategies in performing mental rotation because during their athletic practice they not only manipulate external "objects" (i.e., their opponent) but also have to plan future actions taking into account past experience of these "objects" (for example their weight). All participants reported that lead objects were harder to physically rotate than wooden ones. However, only wrestlers mentally rotated lead objects more slowly than wooden ones—as they would if they were physically rotating them—suggesting the involvement of motor processes. These findings show that the involvement of motor processes in mental rotation depends on specific rather than mere sensorimotor experience.